Estudo comparativo da eficacia de dois adesivos dentinarios e um cimento de ionomero de vidro empregados na adesão do amalgama a dentina - Huhtala, Maria Filomena Rocha Lima [UNESP] (1995)
The purpose of this in vitro study was to determine the shear bond strengths of amalgam to dentin treated with the Amalgambond Plus (AP) and Scotchbond Multi Purpose (SMP) dentin adhesive systems and with the glass-ionomer cement, Vitrebond (V).The buccal and lingual superficial dentin surfaces of thirty extracted human third molars were exposed by wet grinding on 600-grit silicon carbide and the bonding areas demarcated with plastic band matrices (3mm/5umm),fixed in position by the means of a rigid aluminium/teflon mold. The demarcated dentin surfaces were treated with AP, SMP and V as directed by the manufacturers and freshly mixed Dispersalloy amalgam condensed into the plastic matrices. The specimens were then stored in 37°C for 24 hours. The matrices were removed; the shear bond tests performed in an Instron Universal Testing Machine at a cross-head speed of 0.5mm/sec.; and the results expressed in MPa. Some failures were examined in stereomicroscopy. The data were analysed by one-way analysis of variance, Mean failure loads and S.D, were: AP, 2,21 ± 1,5; SMP, 0,33±0,8 e V, 2,63± l,6. Tire shear bond strengths of AP vs V were not significantly different (p>0,05) and SMP was significantly different (p<0,05), Stereomicroscopic analysis demonstrated adhesive failures for SMP (7334%) at the resin/amalgam interface and mixed failures for AP (80%) and for V (933%) within both systems